Utilization of Local Microorganism (MOL) Gained from Stale Rice as Organic Fertilizes for Bok Choy (Brassica chinensis) - Rasyid, Muh. Anwar (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: Rice is one of the main staple foods for Indonesians. The consumption of rice in Indonesian society is increasing every year along with the increasing population of Indonesia. Objective: this Research will test the effectiveness of stale rice MOL organic fertilizer in accelerating the growth rate of Bok choy plants. Method: This Research used experimental research methods to determine the effect of using MOL fertilizer on the growth rate of Bok choy plant height. This research will use a Completely Randomized Design as the design method and with 3 research subjects namely the analytical method to be used in this study is one-way ANOVA with LSD/BNT follow-up test Result and Discussion: it was found that the average growth of plant height given MOL fertilizer on the leaves (S2) had the highest plant growth rate. MOL fertilizer can increase plant height growth 0.2 cm faster than those not fertilized, Conclusions: The results of applying MOL fertilizer to Bok choy plants affect the growth of Bok choy plant height but not significantly. The fastest growth is in the treatment given to the leaves of the plant